2019
DOI: 10.1177/0363546519831008
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Evaluation of the Patient Acceptable Symptom State to Identify Clinically Successful Anterior Cruciate Ligament Reconstruction

Abstract: Background: The length of most patient-reported outcome measures creates significant response burden, which hampers follow-up rates. The Patient Acceptable Symptom State (PASS) is a single-item, patient-reported outcome measure that asks patients to consider all aspects of life to determine whether the state of their joint is satisfactory; this measure may be viable for tracking outcomes on a large scale. Hypothesis: The PASS question would identify clinically successful anterior cruciate ligament reconstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“… 5 Question burden is an important consideration given previous work demonstrating significant impact on follow-up rates, as well as the speed and accuracy with which patients complete instruments. 5 , 20 , 53 The time-to-completion data from the current study demonstrates that SANE, the PROMIS UE CAT, and triad of VAS measures are the quickest to complete, with Constant-Murley, qDASH, and ASES each requiring an average time to completion exceeding 2 minutes 30 seconds. Thus, the VAS measures used in this study represent an important example in which the SANE score can be administered and reported in a domain-specific manner without significantly increasing the time (ie, <45 seconds) or questions (ie, 2 additional).…”
Section: Discussionmentioning
confidence: 68%
“… 5 Question burden is an important consideration given previous work demonstrating significant impact on follow-up rates, as well as the speed and accuracy with which patients complete instruments. 5 , 20 , 53 The time-to-completion data from the current study demonstrates that SANE, the PROMIS UE CAT, and triad of VAS measures are the quickest to complete, with Constant-Murley, qDASH, and ASES each requiring an average time to completion exceeding 2 minutes 30 seconds. Thus, the VAS measures used in this study represent an important example in which the SANE score can be administered and reported in a domain-specific manner without significantly increasing the time (ie, <45 seconds) or questions (ie, 2 additional).…”
Section: Discussionmentioning
confidence: 68%
“… 75 Several studies have since then applied the PASS values for the KOOS and IKDC-SKF when reporting on outcome after ACL treatment. 26 , 42 , 44 , 111 …”
Section: Consensus Statements and Discussionmentioning
confidence: 99%
“…75 Several studies have since then applied the PASS values for the KOOS and IKDC-SKF when reporting on outcome after ACL treatment. 26,42,44,111 A single-item outcome like the PASS summarizes the patient's perception and allows the patient to make an overall statement through a binary answer: "yes" or "no." A numeric scale might have its advantages; however, it is associated with difficulties of interpretation for both patients and researchers.…”
Section: Kiramentioning
confidence: 99%
“…Thresholds for the PASS have been established for the KOOS and the IKDC-SKF by asking the question: “Taking account of all the activity you have during your daily life, your level of pain and also your activity limitations and participations restrictions, do you consider the current state of your knee satisfactory?” alongside the administered PRO [ 76 ]. Several studies have since then applied the PASS values for the KOOS and IKDC-SKF when reporting on outcome after ACL treatment [ 27 , 43 , 45 , 117 ].…”
Section: Patient-reported Outcomementioning
confidence: 99%